The extent to which the rise in the worship of images in the late Middle Ages was influenced by contemporary theories of vision - Joby, Christopher ca. 20./21. Jh. (Scottish journal of theology, 2007)
There are several ways whereby medieval theories of vision may have contributed to the rise of practices some saw as idolatrous. A feature of much medieval art is the rise of naturalistic representation. This process was facilitated by the use of linear perspective, based ultimately on Euclid's visual cone. We are told its application led viewers to confuse a representation with its object. The theory of extramission influenced medieval piety profoundly. First, by suggesting that the eye emits a ray and ‘touches’ its object, it led worshippers to believe that seeing the Eucharistic host had a salvific effect. This may have led them to think that seeing images of saints or God had a similar effect. Second, by implying that the subject was active in the process of seeing, it underpinned Augustine's theory of vision, whereby one trained the eye to access the invisible through the visible. However, as he was aware, the untrained eye could linger on physical objects and want to possess them. Finally, there was much debate about how visual information was mediated. Some argued that it was transmitted by intermediate bodies. The parallels between their language and that used by iconophobes to describe the images they rejected are striking and merit further investigation. Others argued that the viewer had direct access to the object. This understanding, when combined with the idea that seeing equates to knowing, may have led worshippers to believe that seeing an image of God meant they might in some sense know him.